Design, validation and reliability of an instrument for measuring transmedia literacy in undergraduate communication students - Rivera Cervantes, Beatriz Paulina (Emerging Trends in Education, 2024)
Given the lack of standardized instruments to measure transmedia literacy in communication university students, a questionnaire was designed to analyze these skills. This text describes the procedure developed for the design, validation and reliability of an instrument that measures this type of literacy through three dimensions: cognitive, pragmatic and emotional. We applied the Delphi method to validate the theoretical construct and applied the questionnaire to 208 communication students from four universities in the Midwest Region of Mexico. The results indicate that the instrument showed a high internal consistency between the dimensions studied and the items that compose it; therefore, it has the reliability of internal consistency and the necessary validity to be applied when required with stable results.
Keywords: transmedia; literacy; reliability; validity; students